The Worth of Islamic Piety for High-Quality Work Performed by Employees without Fraud - Ilma, Robbi Zidni (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Employees are the most important aspect of every organization, whose success can be determined by its employees whether they have good work quality or not. Good work quality is supported by performance without Fraud. This study aims to determine the role of an employee's Islamic piety value in work quality without Fraud. This is a work with a qualitative research method with an exploratory writing style. Selection of informants using purposive sampling. The primary data presented comes from in-depth and literature study as secondary data. Test the validity of the data as stated in the Triangulation of Sources and Theories technique. For Islamic people, piety is very much related to Fraud prevention, and also every pious employee will implement the teachings of his religion to be professional (not cheating). This research provides an overview to the stakeholders of each organization to find out other aspects in optimizing the quality of work of its employees. Keyword: Syariah Economy; Management; Employees; Work Quality; Fraud